2019
DOI: 10.1101/683946
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A limbic circuit selectively linking active escape to food suppression

Abstract: 1Anorexia Nervosa (AN) is an eating disorder characterized by severe voluntary food 2 restriction 1 . Stress is known to be a precipitating factor in AN 2-5 , but the underlying biology 3 linking stress to feeding is not well understood. Here we describe a novel population of 4 stress-responsive neurons in the lateral septum (LS) that express neurotensin (Nts LS ) and 5 negatively regulate food intake. We used in vivo fiber photometry and chemo/optogenetics 6 to show that Nts LS neurons are activated by stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Following LS lesion, Brady and Nauta (1953) originally described changes in ''general emotional reactivity'' (Brady and Nauta, 1953; see also Spiegel et al, 1940). Subsequently, different authors have attributed specific roles of the LS in anxiety (Chee and Menard, 2013;Parfitt et al, 2017), arousal (Li et al, 2015), aggression (Wong et al, 2016), contextual memory (Besnard et al, 2019;Jarrard, 1993;Leutgeb and Mizumori, 2002;Vouimba et al, 1998), food intake (Azevedo et al, 2019;Scopinho et al, 2008;Yang, 2015, 2016;Terrill et al, 2016), spatial memory (Jaffard et al, 1996;Simon et al, 1986), sexual behavior (Tsukahara et al, 2014), sexually dimorphic social play (Veenema et al, 2013), social preference (Shin et al, 2018), social memory (Leroy et al, 2018;Lukas et al, 2013), reward and addiction (Cornish et al, 2012;Heath, 1963;Luo et al, 2011;McGlinchey and Aston-Jones, 2018;Le Merrer et al, 2007;Olds and Milner, 1954;Sartor and Aston-Jones, 2012;Zahm et al, 2010), gastric motility (Gong et al, 2013), and endocrine responses to stress (Anthony et al, 2014;Usher et al, 1974;Yadin and Thomas, 1996). It remains to be seen whether multiple descending circuits operate in parallel, each with a unique behavioral function, or whether the behavioral phenotypes observed with LS manipulation are aspects of a single corticofugal computation.…”
Section: Routing Of Hippocampal Output To Subcortical Targetsmentioning
confidence: 99%
“…Following LS lesion, Brady and Nauta (1953) originally described changes in ''general emotional reactivity'' (Brady and Nauta, 1953; see also Spiegel et al, 1940). Subsequently, different authors have attributed specific roles of the LS in anxiety (Chee and Menard, 2013;Parfitt et al, 2017), arousal (Li et al, 2015), aggression (Wong et al, 2016), contextual memory (Besnard et al, 2019;Jarrard, 1993;Leutgeb and Mizumori, 2002;Vouimba et al, 1998), food intake (Azevedo et al, 2019;Scopinho et al, 2008;Yang, 2015, 2016;Terrill et al, 2016), spatial memory (Jaffard et al, 1996;Simon et al, 1986), sexual behavior (Tsukahara et al, 2014), sexually dimorphic social play (Veenema et al, 2013), social preference (Shin et al, 2018), social memory (Leroy et al, 2018;Lukas et al, 2013), reward and addiction (Cornish et al, 2012;Heath, 1963;Luo et al, 2011;McGlinchey and Aston-Jones, 2018;Le Merrer et al, 2007;Olds and Milner, 1954;Sartor and Aston-Jones, 2012;Zahm et al, 2010), gastric motility (Gong et al, 2013), and endocrine responses to stress (Anthony et al, 2014;Usher et al, 1974;Yadin and Thomas, 1996). It remains to be seen whether multiple descending circuits operate in parallel, each with a unique behavioral function, or whether the behavioral phenotypes observed with LS manipulation are aspects of a single corticofugal computation.…”
Section: Routing Of Hippocampal Output To Subcortical Targetsmentioning
confidence: 99%
“…Nevertheless, considering the lack of human studies, understanding the neural mechanisms behind these behaviors may provide insight into the development of these complex conditions. Recently, Azevedo et al ( 2020) have identified a group of neurotensin expressing neurons within the LS that specifically act to suppress food intake during active escape, having no effect on the other aspects of the stress response (Azevedo et al, 2020). This suggests that a specific group of neurons exist within the LS that functions solely to inhibit food intake during stress, and supports the idea that the relationship between stress and food may, in part, be mediated by the LS.…”
Section: The Ls-a Link Between Anxiety Depression and Eating Disordersmentioning
confidence: 90%
“…In mice, stimulation of the bed nucleus of stria terminalis (BNST) ➔ lateral hypothalamus (LH) pathway induced binge eating-like behavior [33], amygdala prepronociceptin neurons mediate palatable food consumption [34], and, similarly, unpublished work reported that an insular cortex ➔ central amygdala pathway mediates cue-induced overconsumption [35]. Limbic circuits that specifically mediate suppression of feeding include a lateral septum (LS) ➔ LH circuit that is specifically activated by stress [36] and a paraventricular hypothalamus (PVH) ➔ LS circuit that mediates feeding and anxiety-like behavior [37]. The reasons for the discrepancy between neuroimaging and animal model research is not obvious, but may be due to methodological factors as well as historical predispositions.…”
Section: Trends Trends In In Neurosciences Neurosciencesmentioning
confidence: 98%